Some properties of random evolutions - Yeleyko, Ya. I.; Shurenkov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study asymptotic properties of matrix-valued random evolutions and consider an example of evolutions of this type.